PEMIKIRAN ISLAM TERHADAP MAQASHID AL-SYARIAH DAN HAK ASASI MANUSIA - Supraptono; Mursyid; Muannif Ridwan (Lembaga Marwah Rakyat, 2022)
In this journal article, the researcher will raise the theme and examine the relationship between sharia maqashid and human rights in the view of Islamic legal philosophy, where this preparation uses a literature synthesis process which is a reference in completing article writing. In relation to Islamic civilization and Islamic views where Islam is so really respect and appreciate the differences and equality of rights that exist in humans on this earth. Where the issue of freedom has been raised and made a problem both from the science of law and religion, especially Islam. Humans as social beings and created by Allah SWT as the most perfect creature which has a mind that can be used and utilized to think and to do something that brings good not harm. In the context of human rights itself, where humans are the thing that most people pay attention to. All things and theories are directed at maintaining the welfare and peace between human beings and religious communities so as not to violate each other's rights that already exist in each individual. individual. Therefore, as a stage of classifying these rights, we can use the Maqashid concept which has been implemented and combined with the science of fiqh aulawiyat. However, to make the Maqashid concept more advanced and developing and can be known by the wider community, it is necessary to have smart people so that this concept can work as it should.